Irán y Siria; una política exterior cambiante. Análisis comparado de sus vinculantes internos y sus regiones de influencia. (2013)
In recent years there have been changes in the foreign policy of Syria and Iran; showing how their goals are far from immutable. Typically they have been associated and in some circles they talk of an alliance. However; this paper aims to show that although there is a convergence in a number of issues; their foreign policy priorities put them away. For this; the text is divided into two parts. First; there is a comparison of the internal links that condition the foreign policy in each state. Secondly; regional (and global?) projection of the two nations is contrasted. Throughout the document; the notion of James Rosenau´s comparative study of foreign policy will be taken as a reference.